Extramural but not Extracurricular: Revealing Hidden Learning through the Personal Development Portfolio (PDP) in Architectural Education (EAAE Annual Conference Proceedings, 2020)
This paper considers the introduction of a Personal Development Portfolio into our assessment for architectural education. When revising out undergraduate course structure we moved to a fully integrated model, where assessment was based on a portfolio or ‘body of work’ produced during a ten-week studio project. These projects introduce, develop and integrate understanding and ability of the key knowledge and skills of the curriculum; design, communication, realisation (technology) and contextual studies. Each year of study also includes one unit where professional knowledge is also assessed. Alongside these ‘learning outcomes’ we introduced a PDP: a separate report documenting and reflecting on everything that falls outside the predicted aims of the project.
Keywords: extramural; motivation; collaboration; entrepreneurship; employability